2011
DOI: 10.1002/ps.2174
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbial degradation of neonicotinoid insecticides imidacloprid, acetamiprid, thiacloprid and imidaclothiz and its effect on the persistence of bioefficacy against horsebean aphid Aphis craccivora Koch after soil application

Abstract: Soil microbial activity played a key role in the bioefficacy persistence of neonicotinoid insecticides and therefore significantly affected their technical profile after soil application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
76
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(81 citation statements)
references
References 29 publications
2
76
0
1
Order By: Relevance
“…Lacombe (1999) stated that acetamiprid, the new neurotoxic insecticide belonging to the chloronicotinyl family, is well adapted for orchard protection, with its rapid shock action and persistence (longer than 3 weeks), good control with acetamiprid against the Archives of Phytopathology and Plant Protection 367 main aphids present in pome fruits, stone fruits and citrus (in particular Dysaphis plantaginea, Aphis pomi, and Myzus persicae); it is regularly obtained, equal to or better than standard products. Many authors tested the toxicity of acetamiprid on different aphid species under laboratory and field conditions (Chinnabbai et al 1999;Franco 1999;Chalam et al 2003;Foster et al 2003;Hohn et al 2003;Liu et al 2011;Shi et al 2011). The results indicated that acetamiprid was highly effective for the control of different aphids.…”
Section: Introductionmentioning
confidence: 89%
“…Lacombe (1999) stated that acetamiprid, the new neurotoxic insecticide belonging to the chloronicotinyl family, is well adapted for orchard protection, with its rapid shock action and persistence (longer than 3 weeks), good control with acetamiprid against the Archives of Phytopathology and Plant Protection 367 main aphids present in pome fruits, stone fruits and citrus (in particular Dysaphis plantaginea, Aphis pomi, and Myzus persicae); it is regularly obtained, equal to or better than standard products. Many authors tested the toxicity of acetamiprid on different aphid species under laboratory and field conditions (Chinnabbai et al 1999;Franco 1999;Chalam et al 2003;Foster et al 2003;Hohn et al 2003;Liu et al 2011;Shi et al 2011). The results indicated that acetamiprid was highly effective for the control of different aphids.…”
Section: Introductionmentioning
confidence: 89%
“…Imidaclothiz is transformed in unsterilized soils into the olefin, nitroso, or guanidine derivatives following a degradation pathway which is analogous to that of imidacloprid at the nitroguanidine moiety (Liu et al 2011).…”
Section: New Moleculesmentioning
confidence: 99%
“…[2] If the intermediate metabolites are more toxic to pest insects, they may enhance the bioefficacy of the parent pesticide, which reduces the original applied dosage of pesticide required and therefore decreases its residue in the environment. [3] Neonicotinoids are one of the most important and popular chemical classes of insecticides introduced to the global market. Imidacloprid, 1-(6-chloro-3-pyridylmethyl)-N-nit roimidazolidin-2-ylideneamine (IMI, Fig.…”
Section: Introductionmentioning
confidence: 99%